Formative Assessment: The Elephant in the (class)room. What are teachers’ understandings of, experiences of and views on Formative Assessment in my school context? - Simpson, Angharad (2016)
This inquiry holds as its premise the notion that formative assessment is ill defined and poorly understood by many teachers, and yet it is something that they are required to use regularly and effectively in lessons to achieve the coveted Ofsted / ISI grades of ‘good’ and ‘outstanding’. The inquiry seeks to place formative assessment in the context of the wider landscape of assessment in the UK, discuss various definitions proposed by the critical literature surrounding the subject as well as exploring what it looks like in practice, its benefits and problems. The piece of research conducted saw the researcher interview seven teachers at one independent school using the semi-structured interview method, seeking to uncover teachers’ understandings of and perceptions of formative assessment within that school context. The findings of the inquiry demonstrate that teachers are indeed confused about the definition of formative assessment, and mostly (but not entirely) correspond to the ideas explored in the literature review. Some considerations for future action moving forward and further possible research are briefly discussed.